2008
DOI: 10.1108/14777260810898697
|View full text |Cite
|
Sign up to set email alerts
|

Innovative doctors in Germany: changes through communities of practice

Abstract: The paper presents two original case studies of radical change leading to an integration of healthcare services in Germany. The approach adopted by the German GPs reveals important general lessons for practitioners, as does the analytical framework employed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For example, a qualitative study of two organizations in Germany found that deep knowledge of patient-centered care models and emerging financial models encouraged entrepreneurial physicians to form group practices with new fee structures (e.g. Bosa, 2008). Organizational members with environmental understanding of other stakeholders may be more successful at implementing innovations via relationship building to achieve value alignment with ecosystem partners (Wankah et al, 2022), particularly in LMIS (Bloom and Dees, 2008).…”
Section: Ic Linkagesmentioning
confidence: 99%
“…For example, a qualitative study of two organizations in Germany found that deep knowledge of patient-centered care models and emerging financial models encouraged entrepreneurial physicians to form group practices with new fee structures (e.g. Bosa, 2008). Organizational members with environmental understanding of other stakeholders may be more successful at implementing innovations via relationship building to achieve value alignment with ecosystem partners (Wankah et al, 2022), particularly in LMIS (Bloom and Dees, 2008).…”
Section: Ic Linkagesmentioning
confidence: 99%
“…CoPs allowed professional service firms to analyze new practices, identify critical generative elements, combine learning pathways to networks, and promote knowledge-based organizations (Anand, Gardner, & Morris, 2007;Jawitz, 2009). These innovative structures can offer a unique viewpoint regarding professional advancement in which participants can leverage inquiry and expertise (Ash, Brown, Kluger-Bell, & Hunter, 2009;Dabback, 2010) whereas breaking old practice paradigms to learn new practices (Bosa, 2008).…”
Section: Domainmentioning
confidence: 99%
“…Organized CoPs can promote change in bureaucratic environments such as public health care by promoting entrepreneurial impetus and channeling it into modern tools, radical change, and refined techniques (Bosa, 2008;Elmualim & Govender, 2008). Empirical evidence from longitudinal studies in different industries (from call center organizations to complex innovation working environments) demonstrated that professional CoPs supported the identification of best practices and creative solutions to everyday problems, enabling an environment of innovation and competitiveness (Corso, Giacobbe, & Martini, A., 2009) for private and public organizations alike (Gambarotto & Cammozzo, 2010).…”
Section: Domainmentioning
confidence: 99%
“… Cranfield et al. , 2015 ), or they are only visible as “background” when research focuses on innovative physicians ( Bosa, 2008 ) or entrepreneurs ( Exton, 2008 ). In line with Thune and Mina (2016) , we argue that there is a need for more knowledge on the active role of healthcare organisations in innovation processes and how they can contribute to innovations.…”
Section: Introductionmentioning
confidence: 99%